Studi Komparasi Hasil Belajar antara Pendekatan Kontekstual dan Pendekatan Konvensional dalam Pembelajaran IPS Siswa Kelas VIII SMP Al-Wathan Ambon - Salong, Amjad; Rehatta, Geradin (Universitas Pattimura, 2022)
The effectiveness gap between traditional and student-centered learning approaches necessitates a systematic evaluation. This study aims to compare students’ learning outcomes in social studies using contextual and conventional instructional methods. Employing a quasi-experimental design without a control group, data were collected from two different classes and analyzed using a t-test. The findings revealed that the contextual approach resulted in higher average scores than the conventional method. This highlights the importance of learning connected to real-life experiences. The approach fosters active and collaborative student engagement, leading to more equitable and meaningful academic achievement. This research contributes to the understanding of the impact of context-based instructional strategies in secondary education. The results are relevant for educational policy development and teacher professional growth. It is recommended that contextual learning be broadly integrated into social studies instruction to enhance students’ comprehension and support the development of their critical thinking skills